Determinants of consumer complaint behavior in Mexico - Cruz Rodríguez, Ignacio Javier; Galán Figueroa, Javier (Acta Universitaria, 2019)
This work aims to quantify the determinants of consumer complaint behavior in socioeconomic and business levels. For this purpose, the static panel data methodology is used in order to estimate the impact of consumer complaints both at the federal level of the Mexican Republic and at the level of the main companies that are considered leaders in their field. The results by the state indicate that the complaints are determined by income, reconciliations in favor of consumers and population residing in urban areas. While at the company level, the results show that both market share and company size positively affect consumer complaints. In conclusion, the results agree with the literature reviewed, and a rise in the number of complaints is possible.